2014
DOI: 10.1007/s40138-014-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Current Diagnostic and Therapeutic Strategies in Microvascular Angina

Abstract: Microvascular angina is common among patients with signs and symptoms of acute coronary syndrome and is associated with an increased risk of cardiovascular and cerebrovascular events. Unfortunately, microvascular is often under-recognized in clinical settings. The diagnosis of microvascular angina relies on assessment of the functional status of the coronary microvasculature. Invasive strategies include acetylcholine provocation, intracoronary Doppler ultrasound, and intracoronary thermodilution; noninvasive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…(1) Control of risk factors: angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) are the first choice for patients with hypertension, statins can be used for patients with hypercholesterolemia, active control of blood glucose in patients with diabetes can improve coronary microvascular endothelial function, and obesity can improve CFR by weight loss [27] ;…”
Section: Traditional Treatmentmentioning
confidence: 99%
“…(1) Control of risk factors: angiotensin converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) are the first choice for patients with hypertension, statins can be used for patients with hypercholesterolemia, active control of blood glucose in patients with diabetes can improve coronary microvascular endothelial function, and obesity can improve CFR by weight loss [27] ;…”
Section: Traditional Treatmentmentioning
confidence: 99%
“…Beta-blockers and short-acting nitrates are first-line drugs used to control the symptoms of CMVD ( Task Force et al, 2013 ). Patients who cannot tolerate beta-blockers can be treated with ivabradine instead ( Mumma and Flacke, 2015 ). In the absence of adequate symptom control, the use of calcium antagonists and/or long-acting nitrates in addition to beta-blockers may contribute to improved control of patient symptoms ( Task Force et al, 2013 ).…”
Section: Modern Drug Therapy Of Cmvdmentioning
confidence: 99%
“…It was found that even when adequate and timely reperfusion therapy restored epicardial coronary blood flow, CMVD still occurred in many patients ( Niccoli et al, 2016 ). At present, the main therapeutic drugs used for CMVD are mainly anti-myocardial ischemia drugs, which include beta-blockers, short-acting nitrates, angiotensin-converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARB), calcium channel blockers (CCB), ivabradine, trimetazidine, and ranolazine ( Task Force et al, 2013 ; Villano et al, 2013 ; Mumma and Flacke, 2015 ; Bairey Merz et al, 2016 ; Shah et al, 2017 ). Although these drugs have certain clinical efficacy, many patients still require repeated hospitalization and coronary angiography because of chest pain, which seriously affects patients’ quality of life ( Zhuang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%